2011
DOI: 10.1097/rhu.0b013e31823a46ed
|View full text |Cite
|
Sign up to set email alerts
|

Behçet Disease

Abstract: Although reported elsewhere, Brazilian men with BD did not have a worse prognosis. Women had a higher frequency of arthritis manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…On the other hand, it was observed in countries such as United Kingdom, USA, Germany and Portugal with incidence rates of 0.6, 0.12, 4.16 and 2.4 cases per 100,000 inhabitants, respectively (9)(10)(11) . Although controversial, some studies have shown that men and women are equally affected (9) , with arthritis occurring more frequently in the female population (12) .There is an association between the major histocompatibility complex HLA-B51 allele and BD, which is present in 67.3% of cases (13,14) but the association with environmental factors has also been described (15) .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it was observed in countries such as United Kingdom, USA, Germany and Portugal with incidence rates of 0.6, 0.12, 4.16 and 2.4 cases per 100,000 inhabitants, respectively (9)(10)(11) . Although controversial, some studies have shown that men and women are equally affected (9) , with arthritis occurring more frequently in the female population (12) .There is an association between the major histocompatibility complex HLA-B51 allele and BD, which is present in 67.3% of cases (13,14) but the association with environmental factors has also been described (15) .…”
Section: Introductionmentioning
confidence: 99%